Comment on Activity 6

`d/(dx) tan y`
`=d/(dx) x`
`sec^2 y (dy)/(dx)`
`=1`
`(dy)/(dx)`
`=1/(sec^2 y)`
`(dy)/(dx)`
`=1/(1+tan^2 y)`
`(dy)/(dx)`
`=1/(1+x^2)`
We first apply implicit differentiation to the formula `tan y=x`, where `y=tan^(-1) x:`


 

 

 

 

 

 

`(dy)/(dx)`
`=1/((dx)/(dy))`
  `=1/(d/(dy) tan y)`
  `=1/(sec^2 y)`
  `=1/(1+tan^2 y)`
  `=1/(1+x^2)`
Thus, `d/(dx) tan^(-1) x=1/(1+x^2)`. Now we see that the inverse function formula leads to the same result:

 

 

 

 

It's no surprise that these calculations are so similar, since the inverse function formula was derived by applying the Chain Rule to the defining formula for inverse functions.